Pathological changes induced by repeated percutaneous transluminal coronary angioplasty. Issue 6 (December 1987) - Ueda, M; Becker, A E; Fujimoto, T
Abstract : The histopathological appearances of seven coronary arteries obtained from four patients after repeated percutaneous transluminal coronary angioplasty were analysed. A complex picture was found; typically there were ruptured atherosclerotic plaques, plaque dissection, and a fibrous tissue response. The histopathological appearance of older and more recent fibrous lesions was different. Older lesions contained more collagen and elastin fibres, whereas recent ones had more loosely arranged connective tissue containing abundant glycosaminoglycan and readily identifiable cells. The fibrous tissues tended to be damaged at the sites of previous injury and where the vessel wall was thinnest. In five of the seven arteries there was evidence of a repeated fibrous response to injury with partial or total rupture of the original media. In one instance a repair response within a pre-existing atherosclerotic plaque had caused restenosis. The results indicate that restenosis after repeated percutaneous transluminal coronary angioplasty, like restenosis after a first procedure, is mainly the result of fibrocellular tissue response to injury of the wall tissues. Because older (that is more mature) repair tissue contains fewer cells and more connective elements than younger repair tissue (that is the loosely arranged connective tissue found soon after angioplasty), when it is disrupted by a further angioplasty procedure it is less capable of producing tissue that will obstruct the lumen. This may explain why in the majority of patients with restenosis repeated percutaneous transluminal coronary angioplasty is successful. The present study also showed that occasionally plaque haemorrhages may become organised and incorporated into the pre-existing atherosclerotic lesion.